Effect of banana pseudostem derivative compost and foliar spray of sap on nutrient acquisition, yield and sugar content of corn in tropical soil - Islam, Mahammad Shariful; Khatun, Mst. Fatima; Alam, Md. Khairul; Haque, Mohammad Amdadul; Anik, M.F.A.; Bashar, H. M. Khairul; Hossain, Akbar; Kasim, Susilawati (Springer Science and Business Media Deutschland GmbH, 2024)
Tropical soils are characterized by inadequate fertility, low pH, organic matter, inability to take up nutrients, and lower crop yield. The nutrition provided by organic inputs might have solved some of these problems rather than solo chemical fertilizers. Therefore, a combination of soil amendment with banana pseudostem-based compost and foliar spray of banana pseudostem sap was tested to evaluate the sweet corn’s nutrient uptake, yield, and quality. The study included four levels of banana pseudostem-based co-compost (BPC), viz., CF: control (100% recommended chemical fertilizers); C5: 5 t ha−1; C10: 10 t ha−1; C15: 15 t ha−1; and three foliar frequencies of banana pseudostem sap (BPS), WFS: without application; 2TFS: two; and 3TFS: three times. The treatments were repeated three times, followed by the factorial completely randomized block design. Increasing the dose of compost and foliar sap improved corn growth, yield, and quality. Compared to chemical fertilizers, soil amendment with BPC significantly improved N (7.31%) and P (19.4%) uptake, corn yield (10.6%), and 11.4%, biomass in the 15 t ha−1 compost-treated pot. Similarly, the three foliar sprays of BPS separately increased on average by 8% and 6.5% of cob yield and biomass, respectively over the non-spraying treatment. In contrast, the interaction effects of BPC (15 t ha−1) and foliar spray of BPS (three times) also significantly increased K, Ca, and Mg uptake by 120, 844, and 1823%, respectively, compared with those of the control. Consequently, the phenolic and total sugar content increased by 16.21% and 7.28%, respectively in BPC (15 t ha−1) related to the response of sole chemical fertilizers. Banana pseudostem-based compost at the rate of 15 t ha−1 with three foliar sprays of banana pseudostem sap could increase the productivity and quality of sweet corn in acidic soil.